Automated control system “Smart House” for health and entertainment complex “Bliss”, Rivne - Stetsenko, Anastasia; Havryliuk, Andrii (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
The work is devoted to the development of an intelligent control system of the "Smart House" based on a programmable logic controller.